Optimizing Tomato (Lycopersicon esculentum) Yield Under Salt Stress: The Physiological and Biochemical Effects of Foliar Thiourea Application - Jawaria Abdul Majeed; Safura Bibi; Athar Mahmood; Liaqat Ali; Muhammad Ehsan Safdar; Mahmoud F. Seleiman; Zain Ul Abidin; Bushra A. Alhammad; Muhammad Ahsan Asghar (Plants)
A pot experiment was conducted to investigate the role of thiourea exogenous application (0 mg/L and 100 mg/L) on the morphological, physiological, and yield traits of two varieties of tomato (Naqeeb and Nadir) under different salt stress treatments (0, 60, and 120 mM) in completely randomized design (CRD). The imposition of salinity by rooting medium showed that salt stress reduced plant height by 20%, fresh shoot weight by 50%, dry shoot weight by 78%, fresh root weight by 43%, dry root weight by 84%, root length by 34%, shoot length by 32%, shoot K+ by 47%, Ca2+ by 70%, chlorophyll a by 30%, chlorophyll b by 67%, and the number of seeds per berry by 53%, while shoot Na+ ions were increased by 90% in comparison to those grown with control treatment. However, the exogenous application of thiourea significantly enhanced dry root weight by 25% and the number of seeds per berry by 20% in comparison to untreated plants with thiourea when grown under salt stress. Salt stress resulted in a reduction in the number of berries, weight per berry, number of seeds per berry, and seed weight in both varieties, while thiourea foliar application increased these yield parameters. On the other hand, the Nadir variety surpassed Naqeeb in plant height (+13%), root length (+31%) and shoot length (+11%), fresh shoot weight (+42%) and dry shoot weight (+11%), fresh root weight (+29%), dry root weight (+25%), area of leaf (+26%), chlorophyll a (+32%), and chlorophyll b (+24%). In conclusion, the exogenous application of thiourea can be used to mitigate salt stress in tomato plants since it can improve the growth, physiological, and yield traits of this strategic crop.